Driving Innovation: Exploring What Influences Restaurant Customers' Perception and Adoption of Service Robots in Chengdu, China - Yue, Ou (Scholar: Human Sciences, 2026)
Purpose: This paper investigates the crucial factors of service robots’ significant impact on restaurant customers’ perceived usefulness and intention to use them in Chengdu, China. The conceptual framework provided cause-and-effect correlations between perceived ease of use, perceived usefulness, social image, ability, anthropomorphism, autonomy, and intention to use. Research design, data, and methodology: Restaurant customers in Chengdu, China’s national center city, were given the questionnaire by the researcher using a quantitative method (n=500). Non-probability sampling techniques encompassed judgmental sampling, which was used to choose four hot pot and Sichuan cuisine restaurants; quota sampling, which defined the sample size; and convenience sampling, which was used to gather data and send questionnaires online. The investigator carried out the data analysis, including model fit, reliability, and construct validity, using structural equation modeling (SEM) and confirmatory factor analysis. Results: The findings indicated that each exogenous variable had a significant effect on the corresponding endogenous variable, with Perceived usefulness providing the greatest consequence on Intention to use. Perceived ease of use, social image, Ability, Anthropomorphism, and Autonomy used Perceived usefulness as an intermediate variable to influence restaurant customer’s Intention to use. Conclusions: Organizations, managers, and stakeholders in service robots must focus more on perceived ease of use, usefulness, social image, ability, anthropomorphism, and autonomy using automated systems, which enhance the Intention to use robotic restaurants.